REORIENTING SCIENTIFIC EXEGESIS: A LAKATOSIAN ANALYSIS OF THE QUR’AN-SCIENCE RELATIONSHIP IN THE INDONESIAN MINISTRY OF RELIGIOUS AFFAIRS’ SCIENTIFIC EXEGESIS - Kiki Adnan Muzaki; Waki Ats Tsaqofi (Universitas Nurul Jadid, 2026)
This study examines the practice of tafsīr ‘ilmī (scientific exegesis) in several series of “Tafsir Ilmi” books issued by the Indonesian Ministry of Religious Affairs as a contemporary model for relating the Qur’an and science, a project that articulates explicit interpretive principles meant to mediate between the integrity of revelation and the provisional nature of scientific knowledge. This study aims to assess the consistency between the foundational principles and interpretive practice of tafsīr ‘ilmī, and to evaluate the epistemological implications of this structure for the relationship it constructs between the Qur’an and science. The analysis is taken from three thematic volumes, namely the volumes entitled “Penciptaan Manusia” (The Creation of Humankind), “Penciptaan Bumi” (The Creation of the Earth), and “Kepunahan Makhluk Hidup” (The Extinction of Living Creatures). The data are read through content analysis, drawing analogically on Imre Lakatos’s account of research programmes, in which the foundational principles form a hard core safeguarded by methodological heuristics and the thematic interpretations constitute the protective belt those heuristics produce, so as to test how far practice remains consistent with principle. The study finds that tafsīr ‘ilmī guards the meaning of the Qur’an effectively against scientific reductionism, yet its interpretation remains largely explanatory and confirmatory, leaving the Qur’an’s capacity to raise new scientific questions unactivated. On this basis the article proposes reorienting tafsīr ‘ilmī to affirm the Qur’an as a source of research inspiration, so that scientific interpretation may become a more productive, two-directional exchange between revelation and science.